Validation of the Atomic Absorption Spectroscopy (AAS) for Heavy Metal Analysis and Geochemical Exploration of Sediment Samples from the Sebangan River - Asare, Ebenezer Aquisman; Zaini, Assim; Rafeah, Binti Wahi; Droepenu, Eric Kwabena; Wilson, Festus (Scientific & Academic Publishing, 2019)
This study was to validate the Atomic Absorption Spectroscopy (AAS) in the determination of heavy metals using surface sediments from the Sebangan (estuary of Sadong River), Sarawak State, Malaysia as a case study. Aqua regia procedure was used to extract the trace elements from the sediments. The Scanning Electron Microscope was used to analyse and investigate the microstructure morphology and chemical composition characterizations of the sediments. The results of the examination confirmed to the fact that the technique validated was appropriate and less laborious for the determination of the 12 metals of interest (Al, Mn, Ca, Cd, Cu, Fe, Cr, Ni, Co, Zn and Pb) in the sediment. Massive deposits of sharp teeth granite and quartz particles of distinct tetrahedral conformation with plus size were observed in the samples investigated.